Human and Non-Human Agency as Practical Accomplishment: Interactional Occasions for Ascription and Withdrawal of (Graduated) Agency in the Use of Smart Speaker Technology - Habscheid, Stephan; Hector, Tim; Hrncal, Christine (Social Interaction. Video-Based Studies of Human Sociality, 2023)
The article takes its starting point with heuristics, according to which agency is not to be seen as something that certain ontological entities stably do or do not possess. Rather, it is assumed that agency, especially in voice-based exchange with smart speaker technology, is a dynamic accomplishment, basically bound to the local (linguistic) practices carried out by or rather involving contributions by participants with unequal resources for participating. Following Hirschauer (2016), we distinguish between levels of activity both on an active-passive spectrum as well as on a proactive-inhibitive spectrum and reconstruct empirically against that background how in particular the smart speaker can appear in different situations and contexts. The article concludes with a discussion of the notion of agency relating the observed practices on the one hand and against the background of a broader context of agency as media theory has it on the other, including domestication theory as well as recent smart home technologies and platform logics.